Educational Innovation as a Strategy for Socioeconomic Inclusion in Higher Education in Guayaquil, Ecuador - Parrales Baquerizo, Johnny Reinaldo; Ortega-Cervantes, Erika Annabell; Chilán Tumbaco, Katherine Melissa; Arteaga-Cedeño, Wendy Lilibeth (Scripta Mundi, 2026)
Educational innovation is currently generating multiple expectations for the socioeconomic inclusion of higher education students because it allows access to technological resources and digital tools that facilitate learning, offering quality education to students belonging to priority attention groups. The research shows strategies to promote inclusion in the higher education system, with a focus on students of the Graphic Design program at a university in the city of Guayaquil, Ecuador. This study aims to explore innovative educational practices to address the inequalities that students face throughout their university studies, identifying strategies and proposing improvements in teaching methods. The methodology implemented in this study corresponds to a quantitative and descriptive approach, conducting surveys with a population of 154 university students of Graphic Design program where their experiences in the socioeconomic context of Guayaquil are analyzed, processing data with statistical analysis to measure correlations and trends. The most notable results show in socioeconomic inclusion a favorable perception of access to resources, institutional support and equity of opportunities, strengthening the participation and learning of students, even in the face of economic limitations, perceiving positive and significant relationships between Educational Innovation and Socioeconomic Inclusion. It is concluded that active methodologies and the use of emerging technologies, such as virtual reality, have proven to be effective tools to improve student motivation, participation and learning.